2022
DOI: 10.1186/s40168-021-01198-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced IgA coating of bacteria in women with Lactobacillus crispatus-dominated vaginal microbiota

Abstract: Background Immunoglobulin A (IgA) plays an important role in maintaining a healthy intestinal microbiome, but little is known about the interaction between local immunoglobulins and the vaginal microbiome. We assessed immunoglobulins (unbound and bound to bacteria), their association with vaginal microbiota composition and the changes over time in 25 healthy women of reproductive age. Results In both Lactobacillus crispatus-dominated and non-L. cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…IgA-coated L. jensenii , not IgA-free lactic acid bacterial strains, from the fecal microbiota of a healthy woman significantly inhibits dyslipidemia and gut barrier damage in high-fat diet-fed mice ( 199 ). As mentioned above, IgA-coated bacteria are observed more frequently in vaginal microbiota with L. crispatus dominance compared with that with non- L. crispatus -dominant microbiota ( 84 ). Therefore, IgA-coated L. crispatus as a probiotic might colonize the vagina longer than current probiotic strains.…”
Section: Future Direction and Conclusionmentioning
confidence: 86%
See 2 more Smart Citations
“…IgA-coated L. jensenii , not IgA-free lactic acid bacterial strains, from the fecal microbiota of a healthy woman significantly inhibits dyslipidemia and gut barrier damage in high-fat diet-fed mice ( 199 ). As mentioned above, IgA-coated bacteria are observed more frequently in vaginal microbiota with L. crispatus dominance compared with that with non- L. crispatus -dominant microbiota ( 84 ). Therefore, IgA-coated L. crispatus as a probiotic might colonize the vagina longer than current probiotic strains.…”
Section: Future Direction and Conclusionmentioning
confidence: 86%
“…In contrast, most bacteria in the Firmicutes phylum were not coated with IgA ( 83 ). Of note, Breedveld and colleagues recently reported that higher levels of bacterial IgA coating were observed when the vaginal microbiota was dominated by L. crispatus compared with non- L. crispatus -dominated microbiota ( 84 ). The bacterial IgA coating might modulate biogeography, metabolic processes, proliferation, and survival in mucosal tissue by modifying bacterial gene expression ( 85 , 86 ).…”
Section: Vagina-gut Axismentioning
confidence: 99%
See 1 more Smart Citation
“…L. crispatus is related to defense against infections and regulates anti-inflammatory reactions. Microbiomes, dominated by L. iners , are more likely to transfer to a diverse microbiome than L. crispatus preponderance ( Mitra et al., 2020 ; Breedveld et al., 2022 ). These mechanisms may account for the rise in L. crispatus abundance seen in this study following ES.…”
Section: Discussionmentioning
confidence: 99%
“…Annelot C. Breedvelt et al demonstrated that women with a L. crispatus dominated microbiota had a higher level of bacterial IgA coating compared to non- L. crispatus dominated microbiota. The authors suggested that a higher level of unbound bacteria with IgA in non- L. crispatus dominated microbiota might be associated with inflammation, and therefore a higher susceptibility to infection ( 133 ).…”
Section: Vaginal Microbiota and Stimentioning
confidence: 99%